The Future Prospects of Energy Technologies: Insights from Expert Elicitations - Elena Verdolini; Laura Diaz Anadón; Erin Baker; Valentina Bosetti; Lara Aleluia Reis (Fondazione Eni Enrico Mattei (FEEM), 2016)
Expert elicitation is a process for eliciting subjective probability distributions from experts about items of interest to decision makers. These methods have been increasingly applied in the energy domain to collect information on the future cost and performance of specific energy technologies and the associated uncertainty. This article reviews the existing expert elicitations on energy technologies with three main objectives: (1) to provide insights on expert elicitation methods and how they compare/complement other approaches to inform public energy decision making; (2) to review all recent elicitation exercises about future technology costs; and (3) to discuss the main results from these expert elicitations, in terms of implied rates of cost reduction and the role of R&D investments in shaping these reductions, and compare it with insights from backward looking approaches. We argue that the emergence of data on future energy costs through expert elicitations provides the opportunity for more transparent and robust analyses incorporating technical uncertainty to assess energy and climate change mitigation policies.
Keywords: Q5; Q55; 330; Energy Technologies; R&D Investments; Expert Elicitations; Uncertainty